The Effectiveness of Video Tutorials on Improving Learning Outcomes in Online Learning for Men’s Clothing Courses - Aisyah, St; Suryana, Syarifah; Fitriana, Fitriana (TEKNOBUGA: Jurnal Teknologi Busana dan Boga, 2023)
Video as a tutorial medium is an effective alternative to complement practical learning tools in online learning. This study aims to determine the effectiveness of video tutorials and increase student learning outcomes in online learning in men's clothing courses. This study used a pre-experimental and one-group pretest-posttest design. The research sample is 40 students who program men's clothing courses. Data collection was carried out using a learning achievement test. The result of the data analysis showed that the result of student achievement in learning men's clothing before using the video tutorial could have been more optimal. It shows that some students still need to be more optimal in achieving learning outcomes. Then, the result shows a significant improvement in learning outcomes after implementing video tutorials. The result of inferential analysis, namely the paired t-test, showed differences before and after the application of video tutorials to the reasoning process, especially in the men's clothing courses in fashion design, Home Economics Program, Universitas Negeri Makassar.